Innovation, competition, and productivity growth: Evidence on the impact of growth in Asia's maize seed sector - Spielman, David J.; Kennedy, Adam (International Association of Agricultural Economists, 2015)
Public policies designed to promote seed industry growth in many developing countries are challenged as much by the nature of its primary consumers—small-scale, resource-poor farmers operating in highly fragmented markets—as by the legacy of the structural legacies of a largely public sector-driven system. Although policymakers introduced a wide range of seed policy reforms in many Asian countries as early as the 1980s and 1990s, there have been only a handful of substantive examples where reforms have effected significant change. One reason for slow progress may be that policymakers are insufficiently informed about the opportunities and trade-offs associated with designing laws and regulations that enable the effective governance of seed industry development. As a result, their decisions—and the analytical tools they rely on—tend to be informed by principles, rather than empirical considerations of seed industry development. This paper explores these issues in the context of Asia’s rapidly growing maize seed sector. The paper explores current gaps in the metrics used to analyze the level of competition and innovation in Asia’s maize industry, and more generally, in seed industries throughout much of the developing world. It provides a finite set of indicators designed to better measure competition and innovation in a country’s seed industry to improve research priority-setting and inform policymaking. In turn, it uses these indicators to characterize future scenarios for Asia’s maize seed industry and to recommend policies and investments that might accelerate further seed industry development in the region. Spielman, David J.; Kennedy, Adam